Faktor-Faktor yang Mempengaruhi Kreativitas Akuntan Pendidik - Dian Indri Purnamasari (Jurnal Akuntansi dan Bisnis, 2008)
The existence of ethics problem in auditing profession indicates the need of accountant lecturer to actively involve on ethic values sharing to their student. At this point it is required for accountant lecturer to improve their creativity on teaching methods. The aim of this research is to examine the influence of organizational culture, personality, experience, and degree of intelegentia on accountant lecturer creativity.The result of analysis show that organizational culture in which consist of birocracy and sportivity, personality, and experience influence accountant lecturer creativity. However inovative organizational culture degree of intelegentia and gender do not influence accountant lecturer creativity.